Penyuluhan dan Pendampingan Pembukuan Sederhana Pada UMKM Tahu Tempe Pantura di Desa Tegalrejo - Diya Ayu Rahmawati; Siti Ning Farida (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) are businesses run by small people with limited capital and applying fairly simple technology. One of the UMKM in Tegalrejo Village is Pak Sugik's UMKM Tahu Tempe "Pantura". Based on the results of a field survey, it was shown that in terms of business financial management, UMKM Tahu Tempe Pantura Pak Sugik had not kept bookkeeping. Therefore the purpose of this community service activity is to increase the understanding of Mr. Sugik's "Pantura" Tahu Tempe UMKM regarding the importance of keeping bookkeeping records and understanding how to carry out simple bookkeeping records. The method used in writing this journal is the survey method, the lecture method and the mentoring method. The results of this program of activity are that the UKM Know Tempe "Pantura" Mr. Sugik can be more aware of the importance of keeping bookkeeping records and can keep bookkeeping records independently either by using manual record keeping or digital bookkeeping.